Peru : Second Review Under the Stand-By Arrangement and Requests for Establishment of Performance Criteria Wavier of Nonobservance of Performance Criteria and Rephasing of Future Disbursements 2005 Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Peru. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the Fourth and Fifth Reviews Under the Stand-By Arrangement and Request for Waiver of Applicability discusses Peru's economic performance. Peru's financial markets have only been marginally affected by recent developments in emerging markets. Although further progress has been made with respect to structural reforms, efforts need to be stepped up in some areas. A main challenge in the period ahead will be to reconcile an increase in social spending with prudent fiscal policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet